Human resource performance management in educational organizations - Nuke Irawati; Pompong Budi Setiadi (Institute of Computer Science (IOCS), 2023)
Performance management initiatives, actions, or programs that are started and carried out by an organization's (company's) leadership can be related to planning, directing, and controlling employee performance. The National Education Department at the central level typically oversees HR performance management and educational initiatives, such as planning tasks and the creation of the national curriculum. The purpose of this study is to examine how educational institutions manage their human resources. This study employs a qualitative methodology along with library research techniques. Scientific references are used in data sources and research analysis materials that are collected from books, papers, proceedings, or final projects (thesis, thesis, dissertation). The study's findings suggest that human resource planning initiatives, selection, training and development, performance evaluation/assessment, remuneration, and employment termination procedures comprise human resource performance management in educational institutions. Performance management improvements are carried out continuously to deliver employee, team, and organizational performance to the best. To achieve performance management effectiveness, business organizations need to develop supervision in carrying out performance management improvements